Measuring individual risk preferences - Catherine C. Eckel (IZA World of Labor, 2019)
Risk aversion is an important factor in many settings, including individual decisions about investment or occupational choice, and government choices about policies affecting environmental, industrial, or health risks. Risk preferences are measured using surveys or incentivized games with real consequences. Reviewing the different approaches to measuring individual risk aversion shows that the best approach will depend on the question being asked and the study's target population. In particular, economists' gold standard of incentivized games may not be superior to surveys in all settings.
Keywords: D81; C1; 330; risk aversion; risk preferences; incentivized measures; survey measures